2017
DOI: 10.1080/14634988.2017.1404419
|View full text |Cite
|
Sign up to set email alerts
|

Combining ballast water treatment and ballast water exchange: Reducing colonization pressure and propagule pressure of phytoplankton organisms

Abstract: The International Maritime Organization (IMO) will enforce a new abundance-based performance standard for ballast water in September, 2017. Strong oxidants, like chlorine, have been proposed as a method for achieving this standard. However chlorine treatment of ballast water can produce hazardous trihalomethanes. We assessed maximum trihalomethane production from one chlorine dose for three types of ballast water (fresh, brackish and marine) and three levels of total organic carbon (TOC) concentration (natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 42 publications
1
17
1
Order By: Relevance
“…Land-based and shipboard research on exchange plus treatment determined that the combined approach may benefit freshwater ecosystems by reducing the abundance of high-risk freshwater and euryhaline organisms in discharged ballast water. , Additionally, exchange plus treatment may provide greater reduction in the total abundance and diversity of certain taxonomic groups compared to treatment alone. , This past work focused on specific cause-and-effect relationships without assessing the linked, system-wide effects of a management measure. Estimating the species establishment rate under different ballast water management measures is a useful approach to evaluate the costs and benefits of management measures at scales suitable for decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Land-based and shipboard research on exchange plus treatment determined that the combined approach may benefit freshwater ecosystems by reducing the abundance of high-risk freshwater and euryhaline organisms in discharged ballast water. , Additionally, exchange plus treatment may provide greater reduction in the total abundance and diversity of certain taxonomic groups compared to treatment alone. , This past work focused on specific cause-and-effect relationships without assessing the linked, system-wide effects of a management measure. Estimating the species establishment rate under different ballast water management measures is a useful approach to evaluate the costs and benefits of management measures at scales suitable for decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Briski et al (2015) also found a larger effect of BWE + BWMS on community composition of treated ballast water samples, owing to their targeted research objective to examine voyages having freshwater ballast prior to management. Shipboard studies conducted by Paolucci et al (2015Paolucci et al ( , 2017 similarly found that treatment, alone or combined with exchange, lowered total abundance of viable microplankton (≥10 and <50 µm size class). While Paolucci et al (2015Paolucci et al ( , 2017 found only the combined management method met the D-2 standard, it should be noted that chlorine was applied directly to ballast tanks from the ship's deck without a primary filtration step, so results are not directly comparable with those of BWMS.…”
Section: Discussionmentioning
confidence: 95%
“…As BW exchange will be soon phased out as a management method and replaced by the use of BW treatment systems to meet the D2 standard, 81 the development of methods to assess the efficiency of BW treatment systems on communities is logically gaining more attention. 8,82,83 The use of eDNA metabarcoding has been proposed as a major tool to characterize the difference between communities 21,82,84 and tested on microorganisms. 82 Here, although we had only 2 vessels with treated BW, we also detected an important effect of the BW treatment system as failure with DNA extraction and/or amplification was only observed for vessels with treated BW or for vessel with exchanged BW sampled at the sounding pipe.…”
Section: ■ Discussionmentioning
confidence: 99%